One‐Step Preparation of All‐Natural Pickering Double Emulsions Stabilized by Oppositely Charged Biopolymer Particles (Adv. Mater. Interfaces 23/2021). Issue 23 (8th December 2021) - Li, Yunxing; Gong, Suijing; Guan, Xin; Jiang, Hang; Tao, Shengnan; Yang, Cheng; Ngai, To
Abstract : All‐Natural Pickering Double Emulsions A facile and green one‐step emulsification approach using oppositely charged binary bio‐based particles to readily prepare all‐natural Pickering double emulsion is presented in article number 2101568 by Yunxing Li, Cheng Yang, To Ngai, and co‐workers. The formation of Pickering double emulsion is attributed to the suitable wettability of aggregates formed by binary particles and phase inversion during the emulsion preparation. Furthermore, both hydrophobic and hydrophilic components can be encapsulated and protected.